2004
DOI: 10.1097/01.ju.0000138054.77785.4a
|View full text |Cite
|
Sign up to set email alerts
|

CYSTOMETRIC FINDINGS IN MICE LACKING MUSCARINIC M 2 OR M 3 RECEPTORS

Abstract: The current results confirm that M3 receptor is the principal muscarinic receptor subtype responsible for bladder contraction and the role of M2 receptors is of minor importance. Functional impairments found in M3 KO mice were milder than those elicited by acute blockade of muscarinic receptors by atropine in WT mice, suggesting that noncholinergic mechanisms can compensate for a chronic loss of M3 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 16 publications
6
46
0
4
Order By: Relevance
“…Whereas the M2 subtype is most common, the M3 is functionally more important in producing contraction of isolated bladder, with M2 thought to act by inhibiting beta-adrenergic relaxation in-vivo (Hegde et al, 1997). This is supported by the observation that contractions of bladders from knockout mice without M3 receptors are greatly reduced (Matsui et al, 2000;Igawa et al, 2004). Whereas studies with immunological and Northern Blot techniques have failed to reveal M1 and M4 subtypes, the genes responsible for synthesis of the receptor subtypes M1-M4 have been identified by reverse transcription-polymerase chain reaction (RT-PCR) on whole extracts of rat bladder wall (Braverman et al, 1998a).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Whereas the M2 subtype is most common, the M3 is functionally more important in producing contraction of isolated bladder, with M2 thought to act by inhibiting beta-adrenergic relaxation in-vivo (Hegde et al, 1997). This is supported by the observation that contractions of bladders from knockout mice without M3 receptors are greatly reduced (Matsui et al, 2000;Igawa et al, 2004). Whereas studies with immunological and Northern Blot techniques have failed to reveal M1 and M4 subtypes, the genes responsible for synthesis of the receptor subtypes M1-M4 have been identified by reverse transcription-polymerase chain reaction (RT-PCR) on whole extracts of rat bladder wall (Braverman et al, 1998a).…”
Section: Introductionsupporting
confidence: 55%
“…However, cholinergic contractile responses and their antagonism were similar in male and female rats with comparable pA2 values for darifenacin. A study by Kories et al (Kories et al, 2003) found a similar situation in human and rat tissue using KCl and carbachol challenge, and while it has been shown in M3 receptor knock-out mice that males, but not females, had difficulty urinating, the response of bladder strips were comparable (Matsui et al, 2000;Igawa et al, 2004). Differences between males and females might therefore be explained by urethral properties, as there are important sexual differences in the urethral muscles (Van der Werf and Creed, 2002).…”
Section: Rat Functional Responsesmentioning
confidence: 89%
“…These observations suggest that the M 3 muscarinic receptor subtype is solely responsible for the cholinergic component of nerve-mediated contraction and that compensatory changes by up-regulation of other muscarinic receptor subtypes do not occur in prostates taken from M3R(Ϫ/Ϫ) mice. This does not exclude the possibility of up-regulation of noncholinergic mechanisms such as purinergic mechanisms, as observed in the bladders of M3R(Ϫ/Ϫ) mice (Igawa et al, 2004). However, this seems unlikely in the prostate because the residual contractile response to electrical-field stimulation in prostates taken from M3R(Ϫ/Ϫ) mice is abolished by the ␣ 1 -adrenoceptor antagonist prazosin.…”
Section: Discussionmentioning
confidence: 85%
“…Surprisingly it is the minor population of M3-receptors that mediates detrusor muscle contraction in vitro in all species so far examined (for review see ref 14) including human [15,16] and mouse bladder [17]. Recent studies using mutant mice lacking M2 [18], M3 [19] or both [20] also suggest that the M3 receptor is the predominant muscarinic receptor subtype mediating detrusor contraction in vivo. The present study further supports the idea that M3 receptors are responsible for detrusor contraction in the mouse, since responses to carbachol were antagonised more potently by the M3-antagonist 4-DAMP than the M2-antagonist methoctramine.…”
Section: Discussionmentioning
confidence: 99%